Administrative Factors Influencing Principals’ Effectiveness in Instructional Supervision in Public Secondary Schools in Mukaa Sub-County, Makueni County, Kenya - Muthoka, Jacob Kyengo (My University, 2018)
In Mukaa Sub-county, instructional supervision by principals is yet to be effectively realized. In many cases, teachers do not complete their syllabus and students also register low academic grades in both internal and national examinations. Thus, the purpose of the study was to assess the influence of administrative factors on principals’ effectiveness in instructional supervision in public secondary schools in Mukaa Sub-county, Makueni County, Kenya. The objectives were; to assess the influence of administrative experience, teaching experience, workload and the number of teachers on principals’ effectiveness in instructional supervision in public secondary schools in Mukaa Sub-county. The study was guided by the path-goal theory. The study adopted correlation research design. Target population comprised 40 principals and 380 teachers totaling to 420 respondents from which a sample of 36 principals and 191 teachers were selected based on sampling chart by Krejcie and Morgan (1990). Stratified sampling was applied to create three strata based on the number of zones. From each zone, 12 principals and 64 teachers were selected using simple random sampling. Questionnaires were used to collect data from the respondents. Validity was established through expert judgment. Reliability was established using test retest technique and reliability coefficient, r = 0.79, was obtained using Pearson's Product Moment Correlation Test Analysis which indicated high internal reliability. Data were descriptively analyzed using frequencies and percentages and inferentially using Pearson’s Product Moment Correlation Test Analysis with the help of Statistical Package for Social Science (SPSS 23) and presented using tables and charts. The study established that many secondary schools register low grades in national examinations (KCSE) and that there are numerous administrative factors such as principals’ administrative and teaching experience, workload and the number of teachers which influence principals’ effectiveness in provision of instructional supervision. However, many secondary schools are headed by principals with relatively few years of administration and teaching experience, principals have heavy workload and with very few teachers. Thus, the study recommends that the Ministry of Education through Teachers’ Service Commission (TSC) should promote teachers to positions of school principals based on merit and above all the number of years one has served progressively in positions of headship such as Heads of Departments and Deputy Principals. Teachers should be promoted to headship purely on their experience as erstwhile teachers who have consistently displayed high levels of competence and performance in their classroom teaching. TSC should review the number of lessons principals should undertake to enable them have time to conduct tasks which enhance effective instructional supervision and improved students’ academic performance in national examinations. On the same, TSC should recruit more teachers to cater for the lessons which principals undertake in order to reduce their workload and have time to concentrate on administrative responsibilities. TSC should also recruit more teachers in order to reduce the teacher-student ratio in schools.